2021
DOI: 10.1002/ird.2575
|View full text |Cite
|
Sign up to set email alerts
|

Land suitability and surface water resources potential for irrigation in Becho Plain, upper Awash basin, Ethiopia*

Abstract: In this study, an assessment of the land and surface water resources potential of the Becho Plain was conducted. Land suitability for irrigated agriculture was evaluated by considering the Food and Agriculture Organization (FAO) criteria. The land suitability parameters such as soil properties, slope, land use and land cover were used to identify the suitable irrigable land. The analytical hierarchy process was employed to obtain parameter weights, and later the weighted overlay analysis in the geographic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The irrigation suitability analysis described in the aforementioned sections tries to develop a GIS-based map of distance to water, land use, digital elevation model (DEM) and soil physiochemical parameters of the study areas, as seen in Figures 3-12, which is similar to studies across the world (Gonfa et al, 2021;Hagos et al, 2022;Hussien et al, 2019;Teshome & Halefom, 2020;Tolera et al, 2023;Wubalem, 2023). Additionally, it takes into account the drainage capabilities of soils and their prospective usefulness for irrigation purposes (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The irrigation suitability analysis described in the aforementioned sections tries to develop a GIS-based map of distance to water, land use, digital elevation model (DEM) and soil physiochemical parameters of the study areas, as seen in Figures 3-12, which is similar to studies across the world (Gonfa et al, 2021;Hagos et al, 2022;Hussien et al, 2019;Teshome & Halefom, 2020;Tolera et al, 2023;Wubalem, 2023). Additionally, it takes into account the drainage capabilities of soils and their prospective usefulness for irrigation purposes (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that approximately 27% of the land is highly suitable for irrigation and suggested that the government should enhance the irrigation schemes of this region. Gonfa et al (2021) evaluated suitable irrigated land for surface irrigation of the Becho Plain, Upper Ethiopia, using the AHP. They selected four parameters for the analysis, soil, slope and LULC and used SWAT (Soil and Water Assessment Tool) to analyse the availability of surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Water resource planning for surface irrigation requires information about the land suitability, water availability and water requirements of crops in irrigable areas in time and space [22,23]. Evaluating the potential of water resources and areas suitable for irrigation purposes helps to increase water and crop productivity and cost-effective use of land resources [24,25].…”
mentioning
confidence: 99%